A Case of Hereditary Hemorrhagic Telangiectasia With Gastrointestinal Tract Involvement - Sosi Dzhugarian; Sari Lada; Adnan Ameer; James Tynan Daly (Annals of Internal Medicine: Clinical Cases)
Hereditary hemorrhagic telangiectasia involves the development of arteriovenous malformations which can occur in various organ systems, including the skin and gastrointestinal tract. These small arteriovenous malformations, known as telangiectasias, are most notable on the nose, lips, oral cavity, and fingers. They lead to recurrent bleeds, commonly presenting as epistaxis before age 20 and, less frequently, as gastrointestinal bleeds after the age of 40. We present the case of a patient with anemia who met the criteria for definite hereditary hemorrhagic telangiectasia.